Robot perception errors and human resolution strategies in situated human–robot dialogue. (4th March 2017) - Schütte, Niels; Mac Namee, Brian; Kelleher, John
Graphical Abstract: Abstract: Errors in visual perception may cause problems in situated dialogues. We investigated this problem through an experiment in which human participants interacted through a natural language dialogue interface with a simulated robot. We introduced errors into the robot's perception, and observed the resulting problems in the dialogues and their resolutions. We then introduced different methods for the user to request information about the robot's understanding of the environment. We quantify the impact of perception errors on the dialogues, and investigate resolution attempts by users at a structural level and at the level of referring expressions.